GD2 targeting CAR T cells for neuroblastoma - John Anderson; Giuseppe Barone; Alexandra Zehner (EJC Paediatric Oncology)
Treatment of neuroblastoma is a significant clinical unmet need in paediatric oncology epitomised by high-risk disease in which relapse is common and outcomes for children with relapse or primary refractory disease are typically poor, with 4-year progression-free survival for relapse/refractory disease of 6 %. Immunotherapy targeting disialoganglioside GD2 using monoclonal antibodies (mAb) has become a component of standard of care treatment in neuroblastoma following published studies that have demonstrated clinical activity and survival benefit associated with this treatment. Hence a number of research groups have developed and clinically evaluated chimeric antigen receptor gene modified T cells (CAR-T cells) targeting GD2 in patients with relapsed and refractory neuroblastoma. Preclinical and clinical results using a range of receptor technologies and immune effectors have demonstrated the basic safety and feasibility of this approach, progressing into clinical data exhibiting promise for sustained patient benefit.